2009
DOI: 10.1016/j.jalz.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Early risk assessment for Alzheimer's disease

Abstract: The purpose of the Alzheimer's Association Research Roundtable meeting was to discuss the potential of finding diagnostic tools to determine the earliest risk factors for Alzheimer's disease (AD). Currently, drugs approved for AD address symptoms which are generally manifest after the disease is already well-established, but there is a growing pipeline of drugs that may alter the underlying pathology and therefore slow or halt progression of the disease. As these drugs become available, it will become increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 117 publications
0
21
0
Order By: Relevance
“…By 2050, one million persons will be newly diagnosed and living with symptomatic AD every year (Alzheimer's Association, 2016). Preclinical AD is defined as cognitive normality with biomarker evidence (e.g., brain imaging and cerebrospinal fluid [CSF] assays) that the disease process has begun (Carrillo et al, 2009; Clark et al, 2011; Fagan et al, 2009; Klunk et al, 2004). Individuals with preclinical AD eventually progress to symptomatic AD and will develop cognitive and functional impairments that affect complex activities such as driving (Fagan et al, 2007; Morris et al, 2009; Roe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, one million persons will be newly diagnosed and living with symptomatic AD every year (Alzheimer's Association, 2016). Preclinical AD is defined as cognitive normality with biomarker evidence (e.g., brain imaging and cerebrospinal fluid [CSF] assays) that the disease process has begun (Carrillo et al, 2009; Clark et al, 2011; Fagan et al, 2009; Klunk et al, 2004). Individuals with preclinical AD eventually progress to symptomatic AD and will develop cognitive and functional impairments that affect complex activities such as driving (Fagan et al, 2007; Morris et al, 2009; Roe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CSF biomarkers are based on assays of proteins that are pathologically misfolded, and in addition to Aβ 42 , include tau and phosphorylated tau (ptau 181 ), the principal components of neurofibrillary tangles. 11 Our prior study results have indicated that road test performance, 8 and self-reports of previous involvement in crashes, 12 are cross-sectionally associated with abnormality of these biomarker levels among persons who are cognitively normal.…”
Section: Introductionmentioning
confidence: 95%
“…The validation of indices to identify cognitively healthy individuals at risk for developing the progressive memory symptoms of AD, and to follow these individuals over time is essential for conducting therapeutic trials in this preclinical phase (2). Biomarkers that detect evidence of pathology and are verified for the dementia and MCI phases of AD, e.g., volumetric MRI (3), PET imaging (4) and CSF (5), are under examination in preclinical populations.…”
Section: Introductionmentioning
confidence: 99%